Effects of Rhizoma Parisdis total saponins and its main compounds on gastric emptying via regulating muscarinic receptors in vitro and in vivo. Issue 65 (23rd August 2017) - Wang, Yu; Liu, Yuanxue; Wang, Genbei; Han, Liying; Xia, Ting; Liu, Zhen; Man, Shuli; Gao, Wenyuan; Liu, Changxiao
Abstract : The aim of this study was to explore the inhibitory effect of Rhizoma Parisdis total Saponins (RPS) and the main monomer compounds (polyphyllin I, II, VI and H) on gastric emptying and gastrointestinal motility in vitro and in vivo . Abstract : The aim of this study was to explore the inhibitory effect of Rhizoma Parisdis total Saponins (RPS) and the main monomer compounds (polyphyllin I, II, VI and H) on gastric emptying and gastrointestinal motility in vitro and in vivo . The in vivo experiments demonstrated that mosapride (2.25 mg kg −1 ) and neostigmine (0.1 mg kg −1 ) could promote gastric emptying, while RPS (250 and 500 mg kg −1 ), adrenalin (0.3 mg kg −1 ), atropine (2 mg kg −1 ) and dopamine (1 mg kg −1 ) inhibited gastric emptying. Neostigmine markedly enhanced the delayed gastric motility induced by RPS in mice. The delaying effect of RPS was abolished by atropine and dopamine treatments but not adrenalin. RPS reduced gastric emptying by several pathways, which involved regulating muscarinic receptors. From the in vitro experiments we found that RPS and the main monomer compounds (polyphyllin I, II, VI and H) (20–160 μg ml −1 ) concentration-dependently inhibited the contractions in the antral circular strip compared to untreated controls. Besides, RPS and polyphyllin I, II, VI and H partly prohibited the stimulatory effect of acetylcholine (10 μM) but RPS-induced relaxation was significantly reduced by pretreatment with atropine (10 μM) on gastric antral smooth muscle contractility (GASMC). In addition, we also found that polyphyllin I and II had a stronger inhibitory effect on GASMC than that of polyphyllin VI and H. The experiment indicated that RPS could inhibit the gastric emptying, with polyphyllin I, II, VI and H being the major active ingredients. Meanwhile, the inhibition of gastric emptying and contractions of the antral circular strip by RPS predominantly involves muscarinic receptors.